Effect of the C3a-Receptor Antagonist SB 290157 on Anti-OVA Polyclonal Antibody-Induced Arthritis - Pilaiwanwadee Hutamekalin; Kohei Takeda; Mitsuhiro Tani; Yuko Tsuga; Naoki Ogawa; Nobuaki Mizutani; Shin Yoshino (Elsevier, 2010)
It was investigated whether the C3a-receptor antagonist (C3aRA) SB 290157 was involved in the suppression of anti-OVA pAb-induced arthritis because it is well known that anaphylatoxin C3a plays a crucial role in the development of an effective inflammatory response during complement activation. Anti-OVA pAb-induced arthritis was induced in DBA/1J mice by administration of anti-OVA pAb 0.5 h prior to intra-articular (i.a.) injection of OVA (0 h). Two peaks of joint swelling were observed at 0.5 and 3 h. The role of C3aRA in arthritis was investigated by injection of SB 290157 at concentrations of 10 and 30 mg/kg at 0 and 2 h. The antagonist was able to reduce joint swelling only at 3 h, and about 50% inhibition of joint swelling was observed with the concentration of 30 mg/kg. The C3 level was significantly decreased at 3 h compared with naïve mice showing complement consumption. Furthermore, the C3 activation was observed and increased corresponding to the graded concentration of anti-OVA pAb. The results also revealed that the C3aRA was able to reduce the expression of IL-1β in synovial tissue. Taken together, the results suggested that C3aRA may be effective in the inhibition of arthritis. Keywords:: rheumatoid arthritis, OVA, anti-OVA antibody-induced arthritis, C3a-receptor antagonist, inflammation